2008
DOI: 10.1016/j.chom.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Protein UL38 Inhibits Host Cell Stress Responses by Antagonizing the Tuberous Sclerosis Protein Complex

Abstract: Human cytomegalovirus proteins alter host cells to favor virus replication. These viral proteins include pUL38, which prevents apoptosis. To characterize the mode of action of pUL38, we modified the viral genome to encode an epitope-tagged pUL38 and used rapid immunoaffinity purification to isolate pUL38-interacting host proteins, which were then identified by mass spectrometry. One of the cellular proteins identified was TSC2, a constituent of the tuberous sclerosis tumor suppressor protein complex (TSC1/2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
245
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 178 publications
(253 citation statements)
references
References 60 publications
7
245
1
Order By: Relevance
“…We have previously reported that HCMV-coded pUL38 maintains activity of mTORC1 within infected cells, so that the majority of 4EBP1 is hyperphosphorylated (28). However, a minor portion of 4EBP1 remains hypophosphorylated in infected cells (28), and this is presumably the 4EBP1 that is antagonized by pUL69. It is well established that 4EBP1 is not degraded after HCMV infection (24,29), so it is likely that pUL69 blocks access of 4EBP1 to the m 7 G-cap complex through its contacts with eIF4A1 and PABPC1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that HCMV-coded pUL38 maintains activity of mTORC1 within infected cells, so that the majority of 4EBP1 is hyperphosphorylated (28). However, a minor portion of 4EBP1 remains hypophosphorylated in infected cells (28), and this is presumably the 4EBP1 that is antagonized by pUL69. It is well established that 4EBP1 is not degraded after HCMV infection (24,29), so it is likely that pUL69 blocks access of 4EBP1 to the m 7 G-cap complex through its contacts with eIF4A1 and PABPC1.…”
Section: Discussionmentioning
confidence: 99%
“…Hypophosphorylated 4EBP1 binds to eIF4E and blocks assembly of the cap-binding complex; mTORC1 phosphorylates 4EBP1, and the hyperphosphorylated factor doesn't bind to eIF4E or inhibit translation (18). We have previously reported that HCMV-coded pUL38 maintains activity of mTORC1 within infected cells, so that the majority of 4EBP1 is hyperphosphorylated (28). However, a minor portion of 4EBP1 remains hypophosphorylated in infected cells (28), and this is presumably the 4EBP1 that is antagonized by pUL69.…”
Section: Discussionmentioning
confidence: 99%
“…How is active AMPK decoupled from some of its downstream substrates? The HCMV pUL38 protein binds to TSC2 and prevents TSC1/2 from responding to AMPK phosphorylation (39). Although ACC is induced and required for HCMV replication (34), the mechanism by which it is protected from inactivation by AMPK after infection is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HCMV infection activates signaling pathways that stimulate eIF4F complex formation. For example, HCMV activates the mTOR kinase (13)(14)(15)(16). Active mTOR facilitates eIF4F complex formation by phosphorylating and antagonizing the translation repressor 4EBP-1, which prevents the formation of eIF4F on the mRNA cap (17,18).…”
mentioning
confidence: 99%